2020
DOI: 10.2147/jpr.s223177
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Predictors of Depression, Anxiety and Stress Indicators in a Cohort of Women with Chronic Pelvic Pain</p>

Abstract: Establishing predictors of mental health outcomes is a crucial precursor to the development and assessment of psychological interventions for women with chronic pelvic pain (CPP). The objective of this study was to identify predictors of depression, anxiety and stress in a cohort of women with CPP. Design: Cross-sectional analytic study. Methods: Pre-treatment questionnaires were collected from 212 women with CPP, who had attended a private specialist pelvic pain clinic over a period of 18 months. Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
2
19
0
2
Order By: Relevance
“…Recently, Brooks et al demonstrated that a higher depression score was associated with a currently higher severity of CPP by using the 21-item Depression, Anxiety and Stress Scale in a sample population of 212 women. It has been determined that the severity of depression is dependent upon the severity of pain ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brooks et al demonstrated that a higher depression score was associated with a currently higher severity of CPP by using the 21-item Depression, Anxiety and Stress Scale in a sample population of 212 women. It has been determined that the severity of depression is dependent upon the severity of pain ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most case-control studies, reported that symptoms of depression occurred significantly more often in endometriosis patients compared with healthy controls [28,[30][31][32]35,39,43,46,51,56,62,66,68] but not compared with CPP patients without endometriosis [29,43,48,53,54,56,57,60,62,67]. On the contrary, four studies did not find a higher depression rate in endometriosis patients compared with healthy controls [38,44,57,71].…”
Section: Depressionmentioning
confidence: 97%
“…Finally, 47 articles were included and a systematic qualitative review was performed . Due to variations in study design, lack of control groups, different methods of measuring outcome and due to missing data, only 17 articles were eligible for data-pooling and meta-analysis [28,29,35,38,43,46,38,51,[54][55][56]57,[60][61][62]67,68]. Figure 1 shows a flowchart of the literature review process.…”
Section: Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] In women who suffering from CPP, often accompanied by anxiety, substance abuse or mental disorders. [ 9 , 10 ] Western medicine has limited methods for treating CPP because of special pathological changes: adhesions, scarring, and pelvic congestion.…”
Section: Introductionmentioning
confidence: 99%